The chemistry of carbamates - Mindl, Jaromír; Čegan, Alexandr (Univerzita Pardubice, 2000)
Carbamic acid, H2NCOOH, the half amide of carbonic acid, does not exist as the free acid. Only some heterocyclic carbamic acids form relatively stable compounds. In contrast to this, carbamates including derivatives resulting from replacement of hydrogen atoms at the nitrogen atom by organic radicals form quite stable compounds. The chemistry of carbamates was first reviewed by Adams and Baron [1] in 1965. The carbamate function as considered in this review is based on the trivalent group -O-CO-Nˇ. On attaching various radicals to three free valences of this group, on can obtain many classes of compounds, including the cyclic carbamates as 1,3-oxyzol-2-ones or 1,3-oxazin-2-ones. This article is based on the author's original papers and on some other recently published ones.
Keywords: karbamáty; struktura; analytické metody; deriváty; reakce; organická chemie